Influence of chelating agents on structural, optical, and electromgnetic interference properties of copper selenide nanoparticles synthesized via microwave-assisted method - Garba, Shitu Ibrahim (2021)
Recently, group II-VI binary semiconductor nanomaterials including copper selenide (CuSe), have garnered increased attention due to their remarkable properties that differ significantly from their bulk counterparts, as their functions are highly dependent on particle size, shape, and surface properties. To tune the overall properties of this nanoparticle, various surface modifications are required, such as capping the surface with organic, inorganic, and polymer-based chelating agents which can be used in various applications. In this work, CuSe nanoparticles were synthesized using a simple, low-cost, and environmentally friendly microwave method. Optimization of synthesis conditions such as microwave power, irradiation time, hydrazine hydrate concentration, and copper concentration was carried out to obtain a pure single-phase CuSe nanoparticle. Singlephase CuSe nanoparticles were obtained at 380 W microwave power, 20 minutes of irradiation time, 3 ml of hydrazine hydride, and 0.9:1 copper to selenium molar ratio. The effect of chelating agent concentrations on the structural, morphological, and optical properties of CuSe nanoparticles was fully investigated. Six different chelating agents were used: tartaric acid (TA), ethylenediaminetetraacetic acid (EDTA), citric acid (CA), cetyl ammonium bromide (CTAB), polyvinylpyrrolidone (PVP), and polyethylene glycol (PEG). X-Ray Diffraction (XRD) analysis revealed that all samples formed a pure single-phase hexagonal (Klockmannite) crystal structure. The XRD analysis result is in agreement with the energy dispersive X-ray (EDX) and Raman analysis. At various concentrations of TA, EDTA, CA, CTAB, PVP, and PEG, the average crystallite size estimated using Scherer’s method decreased from 73.10 to 16.10 nm, 73.10 to 16.80 nm, 73.10 to 18.20 nm, 73.10 to 43.60 nm, 73.10 to 14.00 nm, and 73.10 to 21.20 nm respectively. The Williamson-Hall method revealed an estimated crystallite size that is comparable to Scherer's method. The atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM) analysis agree with the obtained XRD results. At various concentrations of TA, EDTA, CA, CTAB, PVP, and PEG, the optical band gap increased from 1.80 to 2.10 eV, 1.80 to 2.20 eV, 1.80 to 2.25 eV, 1.80 to 2.30 eV, and 1.80 to 2.24 eV, respectively. This is attributed to the decrease in particle size of the final product. Besides, photoluminescence (PL) maximum emission for all the samples was centered at 610 nm. The PL intensity was found to increase with increasing chelating agent concentrations in all samples. Other than that, the effect of particle size of CuSe NPs as nanofiller loaded in the PVA polymer matrix on dielectric properties and electromagnetic interference shielding effectiveness (EMI SE) was investigated. The result showed that the dielectric constant, loss factor and loss tangent increases with the decrease in CuSe nanofiller size. This is because smaller particles fill the matrix evenly, forming a chain-like network in the PVA matrix. Moreover, the EMI SE measurement results showed that reflection loss (SER), absorption loss (SEA), and total interference shielding (SET) decreases with an increase in frequency, which is attributed to the impedance mismatch of the EM waves as the applied frequency is increased from 8 to 12 GHz. Additionally, the nanocomposites exhibited a high absorption potential for electromagnetic waves (SEA), but a significant portion of the EM wave was also reflected (SER). The contribution of SER and SEA to SET increased as the size of the CuSe nanofiller is decreased. The nanocomposites showed the SET is higher than the target value of 20 dB. Thus, the results show that incorporating CuSe NPs of various sizes into a PVA polymer matrix significantly improves the total shielding effectiveness of EM waves, implying that the prepared nanocomposites can be used as lightweight, flexible, and low-cost material for electromagnetic interference shielding applications.